Simon P. James, Zen Buddhism and Environmental Ethics - Timmerman, Peter (Journal for the study of religion, nature and culture, 2006)
Simon P. James, Zen Buddhism and Environmental Ethics (Ashgate World Philosophies Series; Aldershot: Ashgate, 2004), pp. 142. Paperback $29.95, £16.99. ISBN 0-7546-1368-2.